Color-tunable Eu2+, Eu3+ co-doped Ca20Al26Mg3Si3O68 phosphor for w-LEDs. Issue 23 (21st May 2019) - An, Zhengce; Liu, Wei; Song, Yanhua; Zhang, Xiangting; Dong, Rujia; Zhou, Xiuqing; Zheng, Keyan; Sheng, Ye; Shi, Zhan; Zou, Haifeng
Abstract : Excellent color-tunable Eu 2+, Eu 3+ co-doped Ca20 Al26 Mg3 Si3 O68 materials have been prepared and their structure related luminescence properties have been studied. Combined with electroluminescent chip, Ca20 Al26 Mg3 Si3 O68 :Eu 2+, Eu 3+ shows multicolour emission. Abstract : A series of promising color-tunable Ca20 Al26 Mg3 Si3 O68 (CAMSO):Eu phosphors have been synthesized by a high-temperature solid-state method. Both Eu 2+ and Eu 3+ ions exist in this system despite the samples prepared in a reducing atmosphere. This phenomenon was discussed according to the thermal stability of the samples and the change of the local structure with Eu 2+ ion doping. Furthermore, the multiple emissions of the Eu 2+ ion in the CAMSO:Eu phosphors arise from Eu 2+ ions at distinct crystallographic sites. The low-temperature emission spectra were investigated in detail by Gaussian peak parting to ascertain the site occupation of the Eu 2+ ions. LEDs were fabricated using the CAMSO: x Eu ( x = 0.1, 0.2, 0.4, and 0.6) with 380 nm chips. The emission color could be tuned continuously from blue to yellow by increasing the concentration of Eu ions. A higher color rendering index ( R a > 80) and a broader color gamut could be achieved, indicating the promising application potential of the CAMSO:Eu phosphors for white LEDs.